2010
DOI: 10.1212/wnl.0b013e3181fc29c9
|View full text |Cite
|
Sign up to set email alerts
|

The MoCA

Abstract: The MoCA is a suitably accurate, brief test when screening all levels of cognition in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
606
8
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(648 citation statements)
references
References 42 publications
26
606
8
8
Order By: Relevance
“…Global cognition was assessed with the MoCA 6, 7. Cognitive testing included the Hopkins Verbal Learning Test‐Revised (HLVT‐R) to assess memory; Benton Judgment of Line Orientation (JOLO) 15‐item version to assess visuospatial function; Symbol‐Digit Modalities Test (SDMT) to assess processing speed‐attention; and Letter‐Number Sequencing (LNS) and semantic (animal) fluency to assess executive abilities‐working memory 8, 9, 10, 11, 12.…”
Section: Methodsmentioning
confidence: 99%
“…Global cognition was assessed with the MoCA 6, 7. Cognitive testing included the Hopkins Verbal Learning Test‐Revised (HLVT‐R) to assess memory; Benton Judgment of Line Orientation (JOLO) 15‐item version to assess visuospatial function; Symbol‐Digit Modalities Test (SDMT) to assess processing speed‐attention; and Letter‐Number Sequencing (LNS) and semantic (animal) fluency to assess executive abilities‐working memory 8, 9, 10, 11, 12.…”
Section: Methodsmentioning
confidence: 99%
“…Global cognition was evaluated by using the Mini-Mental State Examination 28 and the Montreal Cognitive Assessment. 29 In line with the recommendations of the MDS Task Force, specific cognitive domains including memory, executive function, visuospatial function and language, and attention/working memory were also assessed. 30 In this regard, patients were evaluated with the following subtests from the Alzheimer Disease Assessment Scale- [31][32][33] Performances on individual tasks were transformed into z scores.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…The fact that the Hoehn‐Yahr stage of our bilateral PD patients group ranged from 2 to 3 and treatment of PD might explain this absence of significant difference. The MoCA scale is a sensitive and brief test that can be used to screen mild cognitive impairment (Dalrymple‐Alford et al., 2010). When stratified PD patients into cognitive impairment and mild/no cognitive impairment, our results showed that NAA/Cr and NAA/Cho ratios were lower for our patients with mild/no cognitive impairment than healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%